The Organology of Pencak Silat and Reog Ponorogo Dance - Septa Dwi Saputro; Anggono Kusumo Wibowo (Jurnal Seni Tari, 2023)
Pencak Silat is one of the well-developed sports in Indonesia, pencak silat is also a self-defence art that teaches spiritual and physical education to its devotees in living up to the moral values in it. The material object of this research is pencak silat and the formal object is the aesthetics of pencak silat. Through the collaboration of the Reog Ponorogo dance with the pencak silat movement, the aim is to create beautiful new creative movements. The implementation method uses training, practice and history through description, analysis and synthesis. The results of the research are martial arts styles which consist of mental-spiritual aspects, self-defence, arts and sports, and also arts in martial arts divided into wiraga, wirama and wirasa as well as collaboration with the Ponorogo reog arts. The art in pencak silat includes every attitude and movement that is shaped and regulated to achieve maximum artistic beauty. The criteria for art, especially dance, have been used as a guideline. The criteria are formulated with the words wiraga, wirasa, and wirama, which have the meaning of harmony and harmony between the body (raga), taste, and rhythm in displaying every attitude and movement of artistic martial arts which consists of three parts, namely exhibition arts, recreational arts pencak silat, and performance arts pencak silat.